Corporate social responsibility (CSR) practices by SIN firms: Evidence from CSR activity and disclosure. Issue 3 (6th August 2018) - Sharma, Zenu; Song, Liang
Abstract : Purpose: The purpose of this paper is to examine corporate social responsibility (CSR) practices of SIN firms. SIN firms are firms from controversial sectors such as tobacco, alcohol, gambling and firearms. Design/methodology/approach: This paper explains contrasts CSR practices of SIN firms with similar size and industry non-SIN counterparts. Findings: This paper shows that SIN firms conduct more CSR practices than non-SIN firms. This paper also finds that CSR practices of SIN firms are value relevant only when these firms are performing below their peers. Originality/value: The motivation for SIN firms to engage in higher CSR is the competitive advantage hypothesis and not moral rebalancing.